Status of the cardinalfish genus Apogonoides and its type species Apogonoides macassariensis (Percomorpha: Apogonidae) - Fraser, Thomas H.; Bogorodsky, Sergey V. (Zootaxa, 2019)
Apogonoides Bleeker 1849 is identified as the senior synonym of Cercamia Randall & Smith 1988. We present evidence that Cercamia has become well established in the literature. Reversal of priority is proposed for the genus. The type species, macassariensis, is identified with Cercamia eremia (Allen 1987) based on geographic evidence. Reversal of priority is proposed for the species.